2017
DOI: 10.1080/07317115.2017.1347594
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults with Alzheimer’s Disease Who Have Used an Automatic Medication Dispenser for 3 or More Years

Abstract: This article describes four older adults with Alzheimer's disease and comorbidities who used an automatic medication dispenser (AMD) to continue pharmacotherapy for these chronic diseases and who remained at home living either alone or with an older spouse. The AMDs were used for 3 to 4.5 years. The patients scored at least 21 on the Mini-Mental State Examination, and their dosing regimen involved taking the medication once or twice per day throughout this period. The caregivers filled the devices with medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Sleep Disorders inventoryYes 44Schulz R et al [39]2016USA512 – Spouses + Sons +Daughters + Other family members + Friends(251 men; 261 women)Incomplete = 7518–64SurveyEmergency response system; sensors;1. General technology attitudes −10-point scale.No 45Kamimura T [82]2017Japan5 – Spouse + Daughter + Daughter-in-law(Gender not reported)52–65SurveyAutomatic Medication Dispenser1. Carer Burden (1 = no burden; 2 = little burden; 3 = mild burden; 4 = moderate to severe burden).No 46Korchut A et al [83]2017Poland Spain81-(26 men; 54 women)incomplete = 1Not reportedSurveyRobotic assistants1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep Disorders inventoryYes 44Schulz R et al [39]2016USA512 – Spouses + Sons +Daughters + Other family members + Friends(251 men; 261 women)Incomplete = 7518–64SurveyEmergency response system; sensors;1. General technology attitudes −10-point scale.No 45Kamimura T [82]2017Japan5 – Spouse + Daughter + Daughter-in-law(Gender not reported)52–65SurveyAutomatic Medication Dispenser1. Carer Burden (1 = no burden; 2 = little burden; 3 = mild burden; 4 = moderate to severe burden).No 46Korchut A et al [83]2017Poland Spain81-(26 men; 54 women)incomplete = 1Not reportedSurveyRobotic assistants1.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic medication reminder [46, 47, 75, 88]; electronic pill dispensers [10, 35, 59, 69, 82]/ Medicine dispenser with alarm [48, 50]/Medication organiser [81]…”
Section: Resultsmentioning
confidence: 99%
“…The various functions of medication dispensing technologies have been shown to significantly improve medication adherence in community-dwelling older adults with chronic conditions. [12][13][14][15] Studies suggest these kinds of technologies are superior to pill organizers and self-management of medication in helping older adults adhere to their medication regimens. 12,15 Medication dispensing technologies have been shown to improve patient health outcomes, such as reduced frequency of physician visits and hospitalizations, and reduced prescribed medication overtime attributed to the stabilization of patients' conditions due to medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The ndings from this study, in addition to evidence of existing studies, show that medication dispensing technology can improve medication adherence in older adults within the rst week or month, and the high adherence is likely to be maintained over the six month period. 17,31, [33] , [34] Two studies have suggested the possibility of an even longer maintenance of medication adherence for community-dwelling older adults, at two to over three years of use. 18,32 In comparison, the control group had a consistently lower and wider range of medication adherence.…”
Section: Discussionmentioning
confidence: 99%